Comparing Teaching and Administrative Self-Efficacy Among Kindergarten Teachers in an EMI Settings - Rea Erlikasna Ginting (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
The implementation of English-Medium Instruction (EMI) in early childhood education requires teachers to be ready not only for classroom pedagogy but also for meeting institutional documentation duties. This study evaluated the difference in teacher self-efficacy across instructional and administrative domains between English major and non-English major kindergarten practitioners within an Indonesian EMI context. A quantitative approach was used, involving fourteen kindergarten teachers (N = 14) from an integrated international-standard institution in West Kalimantan. Data were gathered through a structured self-efficacy questionnaire and analyzed using the non-parametric Mann-Whitney U test. The findings show that academic specialization did not significantly differentiate instructional self-efficacy in classroom teaching within this study (p = 0.517). Foundational pedagogical skills appeared to compensate within routine interactions in this sample for the absence of a specialized linguistic degree. Conversely, a notable difference was identified within the administrative and reporting domain (p = 0.004, r = 0.74), with non-English major generalists reporting lower self-perceptions of competence when preparing formal curriculum maps, weekly agendas, and written progress updates in English. These findings imply that EMI policy challenges extend beyond active teaching hours into structural documentation duties, suggesting that professional development should prioritize administrative literacy over generic language proficiency training.